2005
DOI: 10.5713/ajas.2005.192
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Serum Protein Profile, Cholesterol and Blood Glucose during Endotoxic Shock in Buffalo Calves Supplemented with Vitamin E and Selenium

Abstract: A study was conducted to monitor the changes in serum protein profile, cholesterol and blood glucose during endotoxic shock in buffalo calves and also to assess the role of prophylactic supplementation of vitamin E and selenium in alleviating the endotoxic effects. Fifteen male buffalo calves (6-8 months of age) were divided into three groups: Group I (control)-infused with 0.9% saline solution; Group II-infused with E. coli endotoxin at 5 µg/kg body weight in normal saline solution; Group III-supplemented pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The LPS directly cause dysfunction of lipid metabolism, thereby causing hepatotoxicity, renal failure and lipid peroxidation via the induction of free radicals 20,22,23 . This study agrees with these metabolic disorders and organ failure caused by LPS.…”
Section: Discussionmentioning
confidence: 99%
“…The LPS directly cause dysfunction of lipid metabolism, thereby causing hepatotoxicity, renal failure and lipid peroxidation via the induction of free radicals 20,22,23 . This study agrees with these metabolic disorders and organ failure caused by LPS.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, Pinotti et al (2004) observed that choline as a component of lipoprotein could increase plasma folate and vitamin E status in periparturient dairy cows. It has been observed that vitamin E has a positive effect on the immune system, and vitamin E supplementation may reduce oxidative stress in periparturient cows (Chatterjee et al, 2003) and buffalo heifers (Kahlon et al, 2004;Sharma et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The immune status of the buffalo calf post-colostrum feeding is influenced also by the vitamin status of the dam: circulating Ig levels were increased by 80% in calves fed colostrum from their dams receiving bolus injections of vitamins A., D 3 and E late in pregnancy (Sikka and Lal, 2005). VitE and selenium also limit the adverse effects of endotoxin from E coli infections associated with many calf rearing systems (Sharma et al, 2005).…”
Section: The Importance Of Colostrummentioning
confidence: 99%